Effect of treatment frequency on the efficacy of superhydrophobic antimicrobial photodynamic therapy of periodontitis in a wistar rat model - Coradi Tonon, Caroline; de Souza Rastelli, Alessandra Nara [UNESP]; Bodahandi, Chathuna; Ashraf, Shoaib; Hasan, Tayyaba; Xu, QianFeng; Greer, Alexander; Lyons, Alan M. (Wiley, 2024)
Superhydrophobic antimicrobial photodynamic therapy (SH-aPDT) is advantageous wherein airborne singlet oxygen (1O2) is delivered from a device tip to kill a biofilm with no photosensitizer exposure and no bacterial selectivity (Gram + or Gram −). For effective treatment of periodontitis, the frequency of treatment as well as the optical light fluence required is not known. Thus, we sought to determine whether single or repeated SH-aPDT treatments would work best in vivo using two fluence values: 60 and 125 J/cm2. We assessed the efficacy of three protocols: single treatment; interval treatments (days 0, 2, and 7); and consecutive treatments (days 0, 1, and 2). After 30 days of evaluation, we found that, SH-aPDT in 3 consecutive treatments significantly decreased Porphyromonas gingivalis levels compared to single and interval SH-aPDT treatments, as well as SRP-chlorhexidine (CHX) controls (p < 0.05). Notably, clinical parameters also improved (p < 0.05), and histological and stereometric analyses revealed that consecutive SH-aPDT treatments were the most effective for promoting healing and reducing inflammation. Our study shows what works best for SH-aPDT, while also demonstrating SH-aPDT advantages to treatment of periodontitis including no bacterial selectivity (Gram + or Gram −) and preventing the development of bacterial resistance.
Keywords: aPDT; chlorhexidine; consecutive days of treatment; handheld device; Porphyromonas gingivalis; repetitive treatments; scaling and root planing; SH-aPDT; singlet oxygen